Effects of Nonsurgical Periodontal Therapy on Clinical Response, Microbiological Profile, and Glycemic Control in Malaysian Subjects with Type 1 Diabetes - Samira Mukhtar Buzinin; Aied Mohammed Alabsi; Alexander Tong Boon Tan; Vui King Vincent-Chong; Dasan Swaminathan (The Scientific World Journal)
The association between diabetes mellitus and chronic periodontal disease has long been established. Most of the researches linking these two very common chronic diseases were based on type 2 diabetes mellitus and chronic periodontal disease. However, this study was conducted to investigate the association between type 1 diabetes and chronic periodontal disease in Malaysian subjects. Forty-one Malaysian subjects, of which 20 subjects were type 1 diabetics and with chronic periodontal disease (test group) and 21 subjects with only chronic periodontal disease (control group), were included in the study. Periodontal parameters and plaque samples for microbiological evaluation were done at baseline, 2 and 3 months after nonsurgical periodontal therapy. Blood samples were taken from only the test group and evaluated for HbA1c at baseline and 3 months after periodontal therapy. There were no statistically significant difference in periodontal parameters between groups (P>0.05) and no significant improvement in the level of HbA1c in the test group. Microbiological studies indicated that there were significant reductions in the levels of the tested pathogens in both groups. The results of our study were similar to the findings of several other studies that had been done previously.